DIFFICULTIES ANALYSIS OF LEARNING ARABIC FOR PADANG STATE UNIVERSITY STUDENTS FROM THE LINGUISTIC ASPECT - Wiza, Rahmi; Amir, Amri; Chaeroni, Ahmad; Afroo, Fakhriyah Annisa (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2024)
This research aims to determine students' difficulties when taking Arabic lectures from the linguistic aspect (phonology and morphology). This is useful for improving the material in the modules provided so that the modules are based on the needs of students at Padang State University. The research method used descriptive quantitative, with informants taken by purposive sampling as many as 55 student representatives from each faculty who attended Arabic language lectures. The results of the research stated that from a linguistic aspect in terms of phonology, students felt about 65.5% of the difficulties were found in 19 letters that were difficult to pronounce, 20 letters that were similar in pronunciation and difficulty in determining the intonation of a vocabulary letter. In terms of morphology, 68.4% of the difficulties were found in differentiating the forms of isim/noun and fi'il/verb, differentiating types of words, determining changes in the form of an object and changes in fi'il. This difficulty causes students to not be maximally active in learning Arabic.